Impact of malaria related messages on insecticide-treated net (ITN) use for malaria prevention in Ghana - Owusu Adjah, Ebenezer S.; Panayiotou, Andrie (My University, 2014)
Background: Media messages have been used in Ghana to promote insecticide-treated net (ITN)/bed net usage in an effort to impact on malaria prevention. The aim of this study was to assess the effect of such malaria-related messages delivered through electronic/print media and by volunteers/health workers on the use of ITNs by children living in a household. Methods. Data was collected from September to November of 2008 using a structured, interviewer-administered questionnaire by the Ghana Statistical Service as part of a national demographic and health survey (DHS). Secondary data analysis was performed on the collected data using multivariate logistic regression for both individual messages and a composite (any of) message variable. Results: From the 11,788 households surveyed, 45% had at least one net. Households with male heads were more likely to have a child sleeping under a bed net the previous night (p = 0.0001). Individual Messages delivered by a health worker or a dedicated radio programme, had the highest effect for one or more children sleeping under a net the night before (OR adjusted = 1.65; 95% CI = 1.44 to 1.88 and OR adjusted = 1.26; 95% CI =1.12 to 1.42 respectively) while hearing any of the eight messages (composite score) resulted in the highest odds for one or more children (OR adjusted = 3.06; 95% CI = 2.27 to 4.12) sleeping under a bed net. Conclusion: Efforts to relate ITN messages to the public are very useful in increasing use of bed nets and having multiple ways of reaching the public increases their effect, with the biggest effect seen when health workers and volunteers were used to deliver malaria-related messages to the public.
Keywords: Bed net; Ghana; Household; Insecticide treated nets; ITN; Media messages